2000
DOI: 10.1108/eum0000000007131
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and evaluation of some economic models of digital‐only journals

Abstract: Economic aspects of digital journal production and delivery were explored using Ithink Analyst, a modelling software package. Three models were developed and simulations were used to monitor the effect of variations in the values of key model elements. The results suggest that scholarly journals can be produced and distributed for a modest fee as long as there are at least 500 subscribers. Alternative models such as author-funded production are also viable. While a model that shares costs between authors and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Halliday and Oppenheim (2000) thought that IoPP's figure was too low, but in my opinion they overestimate editorial staff costs, by underestimating the number of small journals that one staff editor can simultaneously handle. Wood (1998), reporting on the ESPERE project, believed that an all-electronic system for the administration process would save money (as well as time) and bring the figure below the estimates of Donovan (1998), but she produced no numbers to back up this claim.…”
Section: The Amount Of Work Entailed In Rejecting a Paper Is Essentiamentioning
confidence: 93%
“…Halliday and Oppenheim (2000) thought that IoPP's figure was too low, but in my opinion they overestimate editorial staff costs, by underestimating the number of small journals that one staff editor can simultaneously handle. Wood (1998), reporting on the ESPERE project, believed that an all-electronic system for the administration process would save money (as well as time) and bring the figure below the estimates of Donovan (1998), but she produced no numbers to back up this claim.…”
Section: The Amount Of Work Entailed In Rejecting a Paper Is Essentiamentioning
confidence: 93%
“…There has been some confusion in reporting these costs; some writers apparently do not distinguish between donated and paid editor contributions, as well as reviewing and other editor duties. Rowland summarizes past aspects of editorial reviewing activities and concludes the cost is about $200 per submitted paper and $400 per published paper (Donovan, 1998; Halliday, & Oppenheim, 2000; Okerson & McDonnell, 1995; Page, Campbell, & Meadows, 1997; Rowland, 1996, Tenopir & King, 2000). In a survey of 2,165 reviewers, Ware (2009) observed that the respondents had taken about 24 days (elapsed time) to complete their most recent review.…”
Section: Researcher Economicsmentioning
confidence: 99%
“…However, it was suggested that the pricing schemes in the HE market would be best served by a mechanism based on a 'per-page' measure, thus 'allowing for some flexibility in perceptions of value on the part of the rights owner' [12]. In relation to the textbook substitution model recommended by the Bide et al report, Halliday and Oppenheim [15] argued that it is 'prohibitively expensive. We do not believe that this model of charging is viable'.…”
Section: Introductionmentioning
confidence: 99%
“…Halliday and Oppenheim [15] evaluated six economic models of the production and delivery of specific digital library services that derived from the general models above. Four of the models simulated the production of a single journal under varying conditions, and the other two models evaluated were a resource discovery network and a National Electronic Reserve Service (NERS).…”
Section: Introductionmentioning
confidence: 99%